ANALISIS PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN PADA ASTON PONTIANAK HOTEL AND CONVENTION CENTER - B31111013, Erida Susanti Siahaan (Jurnal Manajemen Update, 2016)
Based on the development of the hotel industry in Pontianak with annual hotel construction projects and with an increasing number of hotels implies the development of competition among the hotel management in giving trust to the customer for the quality of their facilities and infrastructures or their services. Pontianak is one of the cities which are considered by the hotel industry investor due to being a transit and strategic town. This research is descriptive and causal, which in form of survey. The sampling techniques used is purposive sampling techniques with the criteria used were the respondent considered to already have a job, minimum age of 17 years, at least has already used the services in the Aston Pontianak Hotel and Convention Center more than once or at least twice and had already used other hotel services in Pontianak. In this research the data is collected with a questionnaire towards 100 customer respondents. The resultÂ  from the collected data shows positive significance influence from sense, act,relate variable towards the customer loyalty in Aston Pontianak Hotel and Convetion Center, while feel, think variable has positive non-significant influence towards the customer loyalty in Aston Pontianak Hotel and Convention Center. Keywords : Experiential Marketing, Sense, Feel, Think, Act, Relate, Customer Loyalty